Globalisation, territory and strategic alliances in different financial centers. - Budd, Leslie (Urban Studies (Routledge))
Presents an assessment of globalization and determines whether a globalized economy is an international one. National impetus given to alliances between markets in major cities; Financial derivatives markets; Impact of electronic trading; Prospect for the incorporation of major players in large financial centers into the governance of urban policy.